Webinar 2: Regional Cooperation for Building a Resilient Seed System in the Philippines - Bertuso, Arma; Baruah, Sampriti (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
A six-member delegation from the Philippines visited Dhaka, Bangladesh and New Delhi, India to explore regional cooperation in the seed sector in January 2020. CIP organized the visit, enabling the delegates to confer with officials who advocate timely availability of newer seeds to strengthen food and nutrition security in the South and Southeast Asian regions and to get updates on seed varieties released through the regional cooperation. The objective of this webinar was to discuss the need, scope, benefits, and challenges of “Regional Seed Cooperation” in developing a climate-resilient seed system in the Philippines.